A foray into the territory of training in the arts of puppetry: teaching and learning - Niculescu, Irina (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
In this article the Romanian director Irina Niculescu talks about her theatrical experience, reflecting on the philosophies of professional training in the Theater of Animated Forms. Keywords: Philosophy. Professional qualification. Theater of Animated Forms.